Extremófilos em astrobiologia: contribuições para a compreensão da produção de bioassinaturas e estratégias moleculares de sobrevivência - Santos, Alef dos (2024)
The origin, evolution, and survival of life in extraterrestrial environments are fundamental questions that drive scientists to search for evidence of life beyond Earth. The science dedicated to investigating these questions is astrobiology, a relatively new field that integrates various areas of the natural sciences, such as astronomy, geology, chemistry, and biology. In this context, the search for habitable environments is essential to explore the possibility of extraterrestrial life. Currently, it is known that some celestial bodies in our solar system, such as Mars and the icy moons Enceladus and Europa, exhibit or have exhibited potentially habitable conditions. However, Earth remains the only known planet that harbors life, serving as the primary guide in this search for answers. This thesis investigates the use of extremophilic microorganisms, such as a black yeast and alkaliphilic bacteria, as models to understand the molecular mechanisms of survival and the production of biosignatures when exposed to conditions that simulate the geochemistry of Mars and the oceans of Enceladus. First, the potential of the black yeast strain Rhinocladiella similis as a eukaryotic model in astrobiological studies was explored. Genomic and proteomic analyses revealed that when exposed to synthetic regolith simulating Martian soil and perchlorate salts, the yeast significantly altered its metabolism, producing various proteins and enzymes to cope with oxidative stress, in addition to activating chemical detoxification processes and increasing melanin production. The yeast also produced unique molecules under these conditions, such as osmolytes, oxylipins, and siderophores. Moreover, the study investigated the potential of a volcanic crater in Saudi Arabia as a promising environment for the discovery of polyextremophilic bacteria that could serve as models in astrobiology. Several halophilic bacteria were isolated and characterized by 16S sequencing, and two of them, from the genus Halalkalibacterium halodurans, were subjected to genomic and metabolomic analyses to investigate their survival capabilities under conditions that simulate the oceans of Enceladus. Their chemical signatures were analyzed using a molecular network approach via mass spectrometry, aiming to identify potential biosignature targets. In summary, this study demonstrated that through multi-omic tools such as genomics, proteomics, and metabolomics, it was possible to deepen the understanding of the molecular strategies employed by these extremophilic microorganisms under astrobiologically relevant conditions, showing that these microorganisms are valuable models for understanding potential life beyond Earth.